FACTORS AFFECTING EARNINGS GROWTH IN MANUFACTURING COMPANIES LISTED IN IDX - Angelina Puspa Wiliasari; Karina Harjanto (Universitas Multimedia Nusantara, 2022)
Abstract— Earnings growth is a change of net income that increases compared to the net profit of the previous period. The purpose of this research is to obtain empirical evidence about the effect of the current ratio, debt to equity ratio, total asset turnover, and managerial ownership on earnings growth. The dependent variable of this research is earnings growth. The independent variable of this research is the current ratio, debt to equity ratio, total asset turnover, and managerial ownership. The data used in this research is secondary data. The samples are selected using purposive sampling. The samples of this study are public manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 period, that has issued audited financial statements at the end of December 31st, using Rupiah as the financial report currency, showing earnings growth, owning and presenting the information of managerial ownership. The research method used in this research is the multiple regression linear method. The results of this study are (1) current ratio has a significant negative effect on earnings growth, (2) debt to equity ratio has a significant negative effect on earnings growth, (3) total asset turnover has no effect on earnings growth, and (4) managerial ownership has no effect on earnings growth. Implication of this study is that companies need to maintain low debt ratio in order to focus in expanding business and growing earnings. Keywords: Current Ratio (CR); Debt To Equity Ratio (DER); Managerial Ownership (MO); Earnings Growth (EG); Total Asset Turnover (TATO)